2014
DOI: 10.1002/ar.23059
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NLRP3, Caspase‐1, and IL‐ 1β Levels in Degenerate Human Intervertebral Disc and Their Association with the Grades of Disc Degeneration

Abstract: The NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome plays an important role in a variety of diseases. However, the role of NLRP3 in the human intervertebral disc (IVD) degeneration remains unknown. In the present study, we assessed the expression levels of the NLRP3 inflammasome and its downstream targets caspase-1 and IL-1b in 45 degenerate and seven nondegenerate IVD samples. The correlation between the degeneration scores and expression levels of NLRP3, caspase-1, and IL-1b were also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 29 publications
7
57
0
Order By: Relevance
“…Others have reported that the degenerative changes of the cartilaginous endplate can result in decreasing nutrient supply, low oxygen tension, and accumulated lactic acid, which accelerate the degeneration process [5,15,45]. Furthermore, cartilaginous endplate degeneration of the internal generation of inflammatory substances can lead to local inflammation through the endplate diffusion and then upregulate inflammatory cytokines and thereby accelerate the pathophysiology of nucleus pulposus degeneration [8,32]. Modic changes are MRI signal changes in the vertebral body adjacent to the endplate, which are correlated with degeneration in the extracellular matrix [6].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that the degenerative changes of the cartilaginous endplate can result in decreasing nutrient supply, low oxygen tension, and accumulated lactic acid, which accelerate the degeneration process [5,15,45]. Furthermore, cartilaginous endplate degeneration of the internal generation of inflammatory substances can lead to local inflammation through the endplate diffusion and then upregulate inflammatory cytokines and thereby accelerate the pathophysiology of nucleus pulposus degeneration [8,32]. Modic changes are MRI signal changes in the vertebral body adjacent to the endplate, which are correlated with degeneration in the extracellular matrix [6].…”
Section: Discussionmentioning
confidence: 99%
“…NOD‐like receptor protein 3 (NLRP3) inflammasomes are essential components of innate immune defense against type 2 diabetes, Alzheimer's disease, and atherosclerosis . Several lines of evidence suggested that excessive activation of the NLRP3 inflammasomes results in the production of downstream caspase‐1 and interleukin (IL)‐1β, which participate in the pathogenesis of IDD and were positively associated with the grades of disk degeneration . Further studies indicated that the activation of thioredoxin‐interacting protein (TXNIP)‐NLRP3 inflammasome signal pathway is closely related to the occurrence and development of IDD .…”
Section: Introductionmentioning
confidence: 99%
“…The inflammasome has been previously shown to play a role in infections [1820], metabolic syndromes [21, 22], autoimmune diseases [2325] and injury [11, 13, 2628]. A positive correlation between the degree of IDD and inflammasome content in the disc has also been previously reported [29]. …”
Section: Introductionmentioning
confidence: 84%
“…Accordingly, higher levels of NLRP3 inflammasome proteins correlate with advanced grades of degenerated discs in humans [29]. We have previously shown that the NLRP1 inflammasome is active in neurons of the spinal cord after injury [13].…”
Section: Discussionmentioning
confidence: 99%